ANALISIS KETERGANTUNGAN DAERAH PERIKANAN SEBAGAI DASAR PELAKSANAAN PROGRAM PEMBERDAYAAN NELAYAN: STUDI KASUS DI KABUPATEN CIREBON DAN INDRAMAYU - Iwan Setiawan; Daniel R. Monintja; Victor P.H. Nikijuluw; M. Fedi A. Sondita (Buletin PSP, 2007)
This paper is a part of the objectives of a study on impacts of fisheries policy, institutional building and individual entrepreneurship to capture fisheries performance. In order to understand the impacts the study on the capture fisheries performance was conducted in Cirebon and Indramayu. As a first step of the study, this study identified fisheries dependences indices for both locations by multi criteria analysis (MCA). In this study, fisheries dependences indices was analysed by five indicator namely ratio of number of fishermen to total resident (fishermen ratio), ratio of total catch in district/citizen level to total catch in province level (catch ratio), ratio of total income district/citizen from fisheries to product domestic regional bruto in province level (income ratio), ratio of total fisheries employment in district/citizen level to total fisheries employment in province level (fisheries employment ratio) and ratio of total number of fisheries vessel in district/citizen level to total number of fisheries vessel in province level. The results showed that although both location operating in a similar overfishing fisheries condition, fisheries dependences indices analysis indicated that Indramayu have higher dependency to capture fisheries activities than Cirebon. From five indicators, Indramayu lead in four indicators (fishermen ratio, catch ratio, income ratio and fisheries employment ratio) comparing to Cirebon that only lead in one indicator (vessel ratio).